Design Innovation For Replica Trophy Using Reverse Engineering And CNC Machining - Mohd Shukor, Nurzayani Nabilah (Universiti Sains Malaysia, 2018)
Trophy is an object that give for a winner in a competition. It comes in many types and in different shape. It is started from ancient Greece where it given for a winner in a war and be design with the details of the war. In traditional way, they create this trophy by using hand. They create the trophy on the wood and even create it on the stone. Making a trophy by using hand takes a lot of time to produce it. With the technology that available in this world, reverse engineering technique is applied to the existing objects then innovate it become something new. Reverse engineering technique is most popular technique that use to create another products that similar to the existing object without having any original document or measurement from the real products. Then by using a 3D scanner it can digitalizing physical objects to create 3D computational geometry. 3D scanners used to capture real object and makes another one in the same shape so that they can be remodeled or analyzed in the digital world. This 3D scanner is the fastest, most accurate, and automated way to acquire. From that can get all the data needed and can improve the actual design to a better design. The object can be modified in the CAD model to correct imperfections and do the improvement by using the suitable software such as CATIA software. CATIA software can provide a surface model or the more complex solid model, whichever results are needed for the application. By using CNC machining to produce the products it can reduce the time taken besides can produce a better surface quality. In this project, the products are choose based on some criteria then it will also undergo with the technique of reverse engineering and producing by using CNC machine. . Then, the parameters of the produced product by using reverse engineering technique will be compared with the design of existing product. Besides, the dimension and size of machining part also be tested. For the parameters comparison result between the outcome product and design of existing product, it contains 5 distance that has been registered to be measure. The percentage different for Distance 1, Distance 2, and Distance 3, Distance 4 and Distance 5 are 4.20%, 5.63%, 8.95%. 0.17% and 0.09% respectively.